Effects of plant-soil interactions on grassland carbon dynamics in a changing world - Connell, Robert Kenneth (Kansas State University, 2020)
Plants are a major conduit through which carbon moves between the atmosphere and the terrestrial biosphere. The organic inputs from plants provide energy to soil microbes which fuels microbial extracellular enzyme production. Soil microbial activity determines the proportion of plant organic inputs that remains stored in soil as organic matter or is mineralized and released back into the atmosphere as carbon dioxide. Plant-soil interactions are, therefore, a critical driver of terrestrial carbon cycling. We live in an era of human-driven change which affects every aspect of ecosystem functioning, so it is critical to understand how different global change factors modulate the plant-soil interactions that influence carbon cycling. In this dissertation I focus on the effects of four specific global change factors on plant-soil interactions in a tallgrass prairie ecosystem: (1) land-use change (i.e., fire suppression and bison removal), (2) woody encroachment, (3) plant invasion, and (4) nutrient enrichment. The overall conclusion from my dissertation research is that all four of these global change factors alter plant-soil interactions in ways that change the storage or turnover of soil carbon. First, long-term fire suppression and/or bison exclusion increases soil C content over time. This change in soil C content is associated with an increase in woody plants in the case of fire suppression or an increase in the dominance of warm-season grasses in the case of bison exclusion under a frequent fire regime. Second, potential C mineralization rates under clonal woody shrubs is higher when the microbial community is decomposing proportionally more shrub-derived organic matter, suggesting that the rate of soil C flux may be dependent on how long the soil has been occupied by woody species. Third, the invasive grass Bromus inermis induces legacy effects on soil microbial community composition and soil organic matter (SOM) decomposition rates. These legacy effects persist for at least six months post-invasive grass removal. Finally, phosphorus fertilization stimulates the rate of SOM decomposition in soil undergoing woody encroachment, but nitrogen fertilization does not. Collectively, these results suggest that the effects of many global change factors on carbon cycling is dependent on spatiotemporal context and historical factors. Additionally, since each of the global change factors I studied affected carbon cycling independently, it will be important to study the combined effects of multiple global change factors acting simultaneously in order to better predict how carbon cycles through terrestrial ecosystems as the world continues to change.
Keywords: global change; carbon cycle; plant-soil interactions; ecosystem ecology